Editing texts: notes about Annibal Caro’s letters (Prassi Ecdotiche della Modernità Letteraria, 2020)
The essay wants to review the stages of writings of some literary works which Annibal Caro is involved in the role of author or reviser, in collaboration with editors as Antonio Blado and Paolo Manuzio, attending their manuscript or printed tradition. Further, a close study of the letters of Annibal Caro allow to trace the historical and the cultural background that influenced the composition of a text, earlier or later his printing.